2013
DOI: 10.4168/aair.2013.5.5.301
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Skin Sensitivity to Aeroallergens

Abstract: PurposeWe previously demonstrated seasonal variation in sensitization to aeroallergens in a small group of patients with exercise-induced asthma. This study was performed to confirm the relationship in a much larger population.MethodsThe charts of 1,891 patients who received allergy skin prick tests were reviewed retrospectively. The test results from subjects aged ≤60 years were compared between the groups classified according to the season when the patients received the tests (spring: March-May, summer: June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
10
1
4
Order By: Relevance
“…Cat allergen exposure is believed to be involved in 29% of asthma cases in the United States of America where 17% of the population is estimated to be sensitized to cat allergens (14). Cat is a popular pet all over the Kingdom of Saudi Arabia and could possibly be related to over 50% cat allergen sensitization observed in the present study.Seasonal variation in skin test reactivity to cat allergen has been reported with less frequent occurrence during summer time (15). However, the reactivity to cat allergen remained high for almost ten months in the present study both in winters and in summers.…”
Section: Discussion:-contrasting
confidence: 58%
“…Cat allergen exposure is believed to be involved in 29% of asthma cases in the United States of America where 17% of the population is estimated to be sensitized to cat allergens (14). Cat is a popular pet all over the Kingdom of Saudi Arabia and could possibly be related to over 50% cat allergen sensitization observed in the present study.Seasonal variation in skin test reactivity to cat allergen has been reported with less frequent occurrence during summer time (15). However, the reactivity to cat allergen remained high for almost ten months in the present study both in winters and in summers.…”
Section: Discussion:-contrasting
confidence: 58%
“…The relative risk for asthma symptoms and airway hyper-responsiveness (AHR) in HDM-sensitive children is 6.71 2. The concentrations of, and sensitization rates to, HDM allergens are higher in autumn than in summer,3 and exercise-induced asthma is highly prevalent and more severe in winter in accordance with the more frequent and severe sensitization to HDM in winter than in summer 4…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Choi SI et al, (22) they also demonstrated seasonal variation in Allergy symptoms correlated with SPT positivity for number of Allergens, especially for pollens.…”
Section: Results and Analysismentioning
confidence: 99%